Analisis Ketaatan Beribadah Terhadap Kecerdasan Akademik: Perspektif Al-Qur’an Surah Al-Baqarah Ayat 282 - Juli Hardian; Hidayat; M. Habibullah; Abdullah Firdaus; Khafifatul Auliya Rahmy; Siti Aminah (UIN Sulthan Thaha Saifuddin Jambi, 2024)
This research aims to study the relationship between devotion to worship and academic intelligence, by focusing on the perspective contained in the Al-Qur'an Surah Al-Baqarah verse 282. Researchers want to understand how devotion to worship, as explained in this verse, can influence academic intelligence. The research method used is text analysis of the Koran and literature studies relevant to education. Researchers studied verses from the Koran to understand the concept of obedience to worship and then reviewed literature related to education to understand how obedience to prayer affects academic intelligence. It is hoped that the findings from this research will provide valuable insights for educators, students and researchers. Educators can use these findings to develop educational programs that help improve their religious devotion and academic intelligence. So they can use these findings to understand how devotion to worship can help them achieve success in the studies they are currently undertaking. Researchers can use these findings to conduct further research on the relationship between obedience to prayer and academic intelligence. Keywords: obedience in worship, academic intelligence, al-qur'an, surah al-baqarah verse 282